MAKANAN TAMBAHAN DENGAN INDEKS GLIKEMIK TINGGI UNTUK PEMENUHAN GIZI ANAK SEKOLAH - Uken S.S. Soetrisno (Persagi, 1999)
High Glycaemic Snack Foods for Nutrition Completion of School Children.School lunch program had been launched since 1996, but there is still some problem especially related to the portion size and portion's nutritional value. This study tried to developed snack foods for school children with portion size of 300 Kcal and 5-7 g protein, and evaluated for their glycaemic index and organoleptic quality. Basic ingredients for food formulation were carbohydrate sources: rice, glutinous rice, cassava, or sago; protein sources: soybean, chick peas, peanut, mungbean or tempe; besides other ingredients such as sugar, coconut oil, grated coconut or coconut milk those were added to increase palatability and energy content. Carbohydrate and protein sources were processed under optimal treatment, which were: soaking at pH 5.8-9.6 and followed by overnight drying and roasting at 75-125o C for 30 minutes. Those treatments were to reduce portion size and to increase the glycaemic index. This study involved adult women and school children to evaluate the portion size and the organoleptic quality. Snack foods in form of smooth or coarse sweet jellied dough had good acceptability. The glycaemic index of 15 snack foods are varied between: 64-99. These indexes are considered as moderate to high. Further study is needed to evaluate the energy effectiveness of the snack foods on maintaining and enhancing the work performances of school children.Keywords: formulated food, nutrients, organoleptic evaluation, glycaemic index.